Darfur diaries : stories of survival - Marlowe, Jen.; Bain, Aisha; Shapiro, Adam.; Rusesabagina, Paul, 1955-; Deng, Francis Mading, 1938- (New York : Nation Books, 2006)
"In November 2004 three independent filmmakers traveled to eastern Chad and crept across the border into Darfur. Improvising as they went, they spoke with dozens of Darfurians, learning about their history, hopes, fears, and the resilience and tragedy of their everyday lives"--Cover, P. [4].
Keywords: Humanitarian assistance -- Sudan -- Darfur; Atrocities -- Sudan -- Darfur; Documentary films -- Production and direction; Darfur (Sudan)